Personal motivation, self-regulation barriers and strategies for weight loss in people with overweight and obesity: a thematic framework analysis. Issue 9 (22nd September 2022) - Chew, Han Shi Jocelyn; Gao, Yujia; Shabbir, Asim; Lim, Su Lin; Geetha, Kayambu; Kim, Guowei; Chong, Choon Seng; Lomanto, Davide; So, Bok Yan Jimmy
Abstract: Objective: To explore motivations, self-regulation barriers and strategies in a multi-ethnic Southeast Asian population with overweight and obesity. Design: Qualitative design using semi-structured face-to-face and videoconferencing interviews. Data were analysed using thematic framework analysis and constant comparison method. Setting: Specialist weight management clinic. Participants: Twenty-two participants were purposively sampled from 13 April to 30 April 2021. Median age and BMI of the participants were 37·5 (interquartile range (IQR) = 13·3) and 39·2 kg/m 2 (IQR = 6·1), respectively. And 31·8 % were men, majority had a high intention to adopt healthy eating behaviours (median = 6·5; IQR = 4·8–6·3) and 59 % of the participants had a medium level of self-regulation. Results: Six themes and fifteen subthemes were derived. Participants were motivated to lose weight by the sense of responsibility as the family's pillar of support and to feel 'normal' again. We coupled self-regulation barriers with corresponding strategies to come up with four broad themes: habitual overconsumption – mindful self-discipline; proximity and convenience of food available – mental tenacity; momentary lack of motivation and sense of control – motivational boosters; and overeating triggers – removing triggers. We highlighted six unique overeating triggers namely: trigger activities (e.g. using social media); eating with family, friends and colleagues; provision of food by someone; emotions (e.g. feeling bored at home, sad and stressed); physiological condition (e.g. premenstrual syndrome); and the time of the day. Conclusions: Future weight management interventions should consider encompassing participant-led weight loss planning, motivation boosters and self-regulation skills to cope with momentary overeating triggers.